Study of a Torque Limiter Based on NiTi Pseudoelastic Tapes. Issue 1 (15th September 2021) - Nespoli, Adelaide; Bassani, Enrico; Villa, Elena; Passaretti, Francesca
Abstract : Herein, a new torsional device based on shape memory alloy elements and operating as torque limiter is presented. It consists of a set of pseudoelastic NiTi tapes working in series configuration. The tapes are assembled radially with respect to the rotational direction and work sequentially in beam‐like bending mode. The trend of the resulting torque may span from pulsating to continuous by changing the number of tapes. Furthermore, the use of NiTi material enables a temperature‐dependent response. Due to the particular mounting, the flag‐shaped pseudoelastic mechanical behavior typical of NiTi is partially hidden; however, the use of pseudoelastic elements provides a stable cyclic response and enables the possibility to tune the output torque. Abstract : Herein, a novel torsional NiTi‐based device is presented. NiTi and the specific design enable several attractive features such as: (i) a peculiar functioning that spans from pulsating to continuous; (ii) a stable and a temperature‐dependent response. Moreover, the output torque can be tuned by increasing the number of NiTi elements as well as by changing the functioning temperature.